Description of Eniacomorpha hermetiae Delvare sp. n. (Hymenoptera, Chalcidoidea, Chalcididae) a pupal parasitoid of Hermetia illucens (L.) (Diptera, Stratiomyidae), and a potential threat to mass production of the fly as a feed supplement for domestic animals - Delvare, Gérard; Copeland, Robert S.; Tanga, Chrysantus M. (Zootaxa, 2019)
Eniacomorpha hermetiae Delvare sp. n. (Hymenoptera, Chalcididae, Dirhininae), reared from pupae of black soldier fly (BSF), Hermetia illucens (Linnaeus, 1758) (Diptera, Stratiomyidae), is described and illustrated from Africa and compared with other similar species newly considered as forming the ehrhorni species-group within Eniacomorpha Girault, 1915. The newly described parasitic wasp may have a negative impact on efforts to mass produce BSF in Africa as a feed supplement for domestic animals. Eniacomorpha is removed from synonymy under Dirhinus Dalman, 1818, revised status, for the Afrotropical species of Dirhininae previously placed in Dirhinus subgenus Pareniaca Crawford, 1913. A checklist of the 10 recognized species of Afrotropical Eniacomorpha is given, of which 9 are new generic combinations.